Drivers of social responsibility disclosure: the moderation of the president director's busyness and political connections - Ceicilia Bintang Hari Yudhanti; Bambang Tjahjadi (Emerald Publishing Limited, 2021)
This study aims to examine the effect of company size on social responsibility disclosure. In addition, this study examines the president director's busyness and political connections in moderating the association between company size and disclosure of corporate social responsibility.The data used in this study were secondary data which included 1,165 observations (company-year). The analysis technique used was multiple regression method and the analysis was carried out by employing STATA software.Researchers found that company size has a positive effect on social responsibility disclosure. The busyness of the president directors and companies connected to politics significantly weakens the association between company size and disclosure of social responsibility.This study uses only one measure of the driving force of social responsibility disclosureThis study contributes to the social responsibility literature by examining the effect of company size on social responsibility. Information on social responsibility disclosure has been carried out by companies in Indonesia; however, it is indicated that only large companies provide sufficient information on social responsibility.Stakeholders can find out information on social responsibility carried out by the company.Companies with busy CEOs and politically connected firms weaken the association between company size and disclosure of social responsibility.